Controlled freezing studies as a corollary selection method for winterhardiness in perennial flax. Issue 5 (9th July 2022) - Tork, David G.; Anderson, Neil O.; Wyse, Donald L.; Betts, Kevin J.
Abstract: Perennial flax ( Linum spp .) breeding objectives at the University of Minnesota (UMN) are to develop agronomic (oilseed, fiber) and horticultural (cut flower, garden perennial) varieties that are hardy in Minnesota (USDA Plant Hardiness Zones 3 and 4). The objective of this research was to determine the range of cold hardiness in UMN perennial flax breeding populations compared with wild accessions of L. austriacum, L. lewisii, and L. perenne . Fifty‐three genotypes from seven populations were low temperature acclimated, followed by controlled freezing using a programmable freezer. The observed lethal temperature for 50% plant kill (LT50 ) ranged from >0 °C (0% survival) to <−12 °C (100% survival), for the test temperatures of 0, −4, −8, −10, and −12 °C. Cold damage was measured after 4 wk of regrowth as the proportion of alive shoots and a root damage rating. Significant negative correlations were observed between LT50 and proportion of alive shoots ( r = −.918) and root damage rating ( r = −.935). Both L. austriacum and L. perenne had significantly less cold damage than L. lewisii and the breeding populations. This study establishes methods of screening perennial flax cold tolerance that are more cost effective, rapid, and repeatable compared to field evaluations. Core Ideas: Controlled freezing tests were useful to identify hardy perennial flax species and genotypes. Lethal temperatures for 50% plant kill (LT50 ) were as low as ‐12 °C (hardy in MN USDA Z3–4). Linum austriacum and L. perenne had significantly less cold damage than L. lewisii and hybrids.